Self-efficacy and online help seeking tendencies of EFL learners. (1st January 2014) - Ching, Gregory S.; Lin, Mei-Chin; Wang, Wen-Lin; Tchong, Wei-Ling
For engineering students in Taiwan, technology is used in developing their English language competencies. This paper presents the findings of an experimental EFL online learning course. A total of 105 engineering students participated in a semester-long Basic English class. Students are assigned learning tasks that can be accomplished either with their smartphones or tablets-PCs. A survey questionnaire with regards to the students' self-efficacy within an internet-based learning environment, help seeking tendencies, perceived ease of use, intent and actual technology use, and personality was administered. Result shows that students who use smartphones with internet access tends to have more self-efficacy as compared to their peers with no internet access. These students also scored significantly higher in the course than their peers without internet access. SEM was used to validate the influence of self-efficacy and online help seeking tendencies towards the perceived ease of use, intent and actual use of the course.